Analysis of Manufacturing Errors and Its Influence on Meshing Performance of Herringbone Gears - Jie Sun; Xijin Zhang; Xunmin Yin; Haitao Jia; Fang Guo (Jixie chuandong, 2022)
Manufacturing errors are one of the main causes of vibration and noise of gear transmission system，and the combination of multiple errors seriously affects the meshing performance of gear pairs. The influence degree and law of various manufacturing errors on meshing performance of herringbone gear pairs are mainly studied. Firstly，the manufacturing error model is established，and the actual tooth surface is constructed based on the theory of spatial coordinate transformation. Secondly，the influence law of different errors on the meshing performance of the gear pair is explored through the load distribution on the tooth surface，and the influence degree of different errors is explored based on the orthogonal experiment. Finally，the relationship between the influence of typical error types on the meshing performance of gear pairs and the system load is analyzed. The results show that the influence law of various errors on the meshing performance of gear pair is different，and the positive tilt deviation of helix direction has the most prominent influence on the meshing performance of gear pairs under heavy load.